PERANCANGAN APLIKASI KLASIFIKASI SENTIMEN BERBASIS WEB TERHADAP MATA UANG KRIPTO - Fahmi Ilmawan Sulaiman; Wing Wahyu Winarno; Mei Parwanto Kurniawan (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
Sentiment analysis is a collection of opinions that studies opinions about something like an issue, product, event or topic. In deciding to choose cryptocurrency, the majority of Indonesian people tend to only read the latest reviews about cryptocurrencies and even a few will lead to wrong conclusions. To analyze cryptocurrency sentiment easily and quickly, a sentiment analysis system with a convenient and easy-to-use interface is required. The application to analyze this sentiment is web-based which is made using the PHP (Hypertext Preprocessor) framework by applying the MVC (Model View Controller) concept. This application can import data in CSV format which is then processed into an application using the nave Bayes algorithm in the sentiment classification process which is then evaluated by the confusion matrix method. The reviews are taken from social media twitter and it is hoped that this application will be able to provide classification information accurately, precisely and reliably.